Unsupervised analysis of combined lipid and coagulation data reveals coagulopathy subtypes among dialysis patients - Contaifer, Daniel; Carl, Daniel E.; Warncke, Urszula Osinska; Martin, Erika J.; Mohammed, Bassem M.; Van Tassell, Benjamin; Brophy, Donald F.; Chalfant, Charles E.; Wijesinghe, Dayanjan S. (Journal of lipid research, 2017)
Hemodialysis (HD) and peritoneal dialysis (PD) are the primary means of managing end stage renal disease (ESRD). However, these treatment modalities are associated with the onset of coagulation abnormalities. Effective management of coagulation risk among these patients requires the identification of surrogate markers that provide an early indication of the coagulation abnormalities. The role of sphingolipids in the manifestation and prediction of coagulation abnormalities among dialysis patients have never been investigated. Herein, we report the first instance of an in depth investigation into the sphingolipid changes among ESRD patients undergoing HD and PD. The results reveal distinct differences in terms of perturbations to specific sphingolipid biosynthetic pathways that are highly dependent on the treatment modality. Our studies also demonstrated strong correlation between specific sphingolipids and coagulation parameters, such as HexCer(d18:1/26:0) and maximal amplitude (MA), SM(d18:1/24:1) and tissue factor pathway inhibitor, and sphingosine 1-phosphate d18:1 and FX (Spearman ρ of 0.93, 0.89, and −0.89, respectively). Furthermore, our study revealed the potential for using HexCer(d18:1/22:0), HexCer(d18:1/24:0), and HexCer(d18:1/26:0) (r2 = 0.71, 0.82, and 0.63, respectively) and coagulation parameter MA (r2 = 0.7) for successful diagnosis of differential coagulopathies among ESRD patients undergoing HD, providing an opportunity toward personalized disease management.